FAKTOR MAKRO EKONOMI (VARIABEL CRR) PADA RETURN PORTOFOLIO PASAR SAHAM DI INDONESIA SAAT BULLISH DAN BEARISH - Sitinjak, Elizabeth Lucky Maretha (Jurnal Organisasi Dan Manajemen, 2011)
Stock market conditions in Indonesia since 1998 until 2008 is increasing with the 500 IDX Composite can be inflated into 2000s. This becomes interesting factor associated with macro-economic factors that affect the variabel CRR (Chen Roll and Ross). Researchers exam which we form portofiolio into 3 classes, large, medium, and large size companies from multiplying shares outstanding by its stock price. This research periodesasi long enough so that the portfolio is formed only by 15 issuers, this is caused by mergers or acquisitions from the issuer, the issuer is listed on the Stock Exchange from 1998-2008. However, with 11 years of data is very good for macro economic conditions in Indonesia. Independen variabels of this study consisted of changes in inflation expectations (DEIt), unexpected inflation (Uit), unexpected risk free rate (URFt), and the rate of economic growth (GMT) have a significant effect on portfolio return of capital market conditions are bullish for all forms of portfolio. Meanwhile, bearish market conditions only for the portfolio of small and large sizes only. Economic growth rate did not significantly affect the three portfolios in the bearish market conditions, this is because the movement of our stock in Indonesia is still largely influenced by foreign investors.